External assessments, much more than results. PISA at a glance - Vicente Alcañiz Miñano; David Cervera Olivares (ADIDE Federación, 2014)
This article presents the processes of international external assessment and explores the most interesting aspects of such assessments to the education system, with particular emphasis on the Programme for International Student Assessment (PISA). We are used to reading and hearing different types of comments based on the data provided by these assessments, therefore it is necessary to get to know the standardized international assessment processes in order to enable teachers to interpret the data, beyond the overall results, which are useful but only provide partial information that is necessary to analyze thoroughly and deepen to use rigorously for the sake of improvement. An important conclusion to taking into account is that, based on our knowledge of the methods and techniques that underpin these assessments these processes can be introduced into everyday classroom, tailored to each subject, bringing students to an international competence and using their skills to solve problems.